The effect of oregano essential oil on the prevention and treatment of Salmonella pullorum and Salmonella gallinarum infections in commercial Yellow-chicken breeders - Xu, Ziheng; Wang, Can; Li, Changcheng; Wang, Min; Chen, Wenyan; Zhou, Chenyu; Wei, Ping (Frontiers in Veterinary Science, 2022)
In order to prevent pullorum disease and fowl typhoid in breeders, the use of oregano essential oil (OEO) was tested for the prevention and treatment of infections of multidrug-resistant Salmonella pullorum (SP) and Salmonella gallinarum (SG) in commercial Yellow-chicken breeders. In the challenge-protection experiment, commercial Hongguang-Black 1-day-old breeder chicks were randomly divided into four groups, including A (challenged, preventive dose), B (challenged, treatment dose), C (challenged, untreated), and D (unchallenged, untreated). Group A was supplemented with 200 μL/L OEO in the drinking water during the whole trial (1-35 days of age) and group B was supplemented with 400 μL/L OEO during 8–12 days of age, while groups C and D were kept as untreated controls. At 7 days of age, birds of groups A, B, and C were divided into two subgroups with equal number of birds (A1-A2, B1-B2, and C1-C2), and then subgroups A1, B1, and C1 were challenged with SP, while subgroups A2, B2, and C2 were challenged with SG. Clinical symptoms and death were observed and recorded daily. Every week during the experiment, serum antibodies against SP and SG of all the groups were detected by the plate agglutinate test (PAT). At the age of 35 days, all birds were weighed and necropsied, lesions were recorded and the challenging pathogens were isolated. The results showed that the positive rates of SP and SG isolation in groups A1, A2 and B1, B2 were significantly lower (P < 0.05) than those of groups C1 and C2, respectively, while groups A1 and A2 were slightly lower (P > 0.05) than those of groups B1 and B2. The average body weight (BW) of groups A1 and A2 were significantly higher (P < 0.05) than those of groups B1, B2 and C1, C2, respectively, but there was no significant difference (P > 0.05) with that of group D. The r-value between PAT positive and the recovery rates of Salmonella was 0.99, which means they are highly positively correlated. The results of this study demonstrated that the prevention dose (200μL/L) and the treatment dose (400 μL/L) of OEO supplemented in the drinking water could all effectively decrease infections of SP and SG and that the effect of the prevention was greater than that of the treatment and finally that the prevention could also significantly reduce the BW decline of birds challenged with SP and SG.